Strategic leadership style of school principals in selected Islamic private secondary school in Pattani, Thailand - Hatyida-oh, Nasruddeen; Mohd Ali, Hairuddin (2013)
The study hypothesized to examine the underlying factors of strategic leadership style. PCA was applied to arrive at the conclusions. The results of the study supported that the nine-factor model were generated by he data collected form the Islamic private secondary school teachers in Pattani. The purpose of the present research was to examine to underlying factor of strategic leadership style. This research adopts a survey approach. One hundred and seventy eight (178) Islamic private secondary school teachers were selected using simple random sampling. Only seven factors that represent strategic leadership style for Islamic private school principal in Pattani. Findings of the study could establish a new comprehensive framework of the strategic style and will assist educators, administrators and professional development coordinators to adequately prepare, train and support principal to become effective leader. Principal Strategic Leadership Style: It is defined as educational executives who adapt a new way of thinking and acting. More than ever before, strategic educational leadership